2018
DOI: 10.3389/fonc.2018.00404
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Nanoparticles and Dendritic Cells: From the Perspective of Cancer Immunotherapy

Abstract: Dendritic cells (DCs) are the primary antigen-presenting cells and play key roles in the orchestration of the innate and adaptive immune system. Targeting DCs by nanotechnology stands as a promising strategy for cancer immunotherapy. The physicochemical properties of nanoparticles (NPs) influence their interactions with DCs, thus altering the immune outcome of DCs by changing their functions in the processes of maturation, homing, antigen processing and antigen presentation. In this review, we summarize the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 139 publications
(158 reference statements)
3
108
0
Order By: Relevance
“…DC2.4 cells could promptly internalize streptococcal MVs, reaching around 80% of positive cells after an incubation period of 30 min. This may suggest a specific receptor-mediated and/or endocytosis uptake mechanism for antigen-carrying MVs into APCs as has been reported in literature (44). There is negligible uptake of liposomes by DC2.4 cells after 30 min, suggesting a specific interaction between DC2.4 cells and streptococcal MVs.…”
Section: )supporting
confidence: 77%
“…DC2.4 cells could promptly internalize streptococcal MVs, reaching around 80% of positive cells after an incubation period of 30 min. This may suggest a specific receptor-mediated and/or endocytosis uptake mechanism for antigen-carrying MVs into APCs as has been reported in literature (44). There is negligible uptake of liposomes by DC2.4 cells after 30 min, suggesting a specific interaction between DC2.4 cells and streptococcal MVs.…”
Section: )supporting
confidence: 77%
“…The ease of functionalization allows the delivery of a variety of cargos to the cells. Such a quality is exploited in immunotherapies, where AuNP are conjugated with specific antigens or agents triggering the activation of immune response cells [41,42] or antibodies' production [43]. Such therapies hold a promise for cancer and infectious diseases treatment.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…For initial recognition of the pathogen or cancerous cells in the body, antigen-presenting cells (APCs) such as dendritic cells (DCs) are responsible for phagocytosing the tumour-associated antigen (TAA) and subsequently presenting it to the T-cells to induce the adaptive immune response [6]. One current immunotherapeutic strategy involves vaccinating the patient through stimulating the maturation of the DCs ex vivo with TAA antigens, then transferring the DCs back into the body to increase antigenspecific responses ( Figure 1) [1].…”
Section: The Role Of Nanoparticles In Dcmediated Immunotherapymentioning
confidence: 99%
“…For example, a study published in 2017 found that intravenously administered liposomes carrying TAA-coding RNA was able to e ciently target DCs by adjusting the net charge of the liposome (Figure 1) [1]. Similarly, surface modification can also dictate the antigen uptake, with studies indicating that smaller, hydrophobic, and cationic NPs are correlated with greater internalization and interaction with the DCs [6]. Despite these enhancing functions of the NPs, studies have found impaired antigen-processing ability with NPs like graphene oxide.…”
Section: The Role Of Nanoparticles In Dcmediated Immunotherapymentioning
confidence: 99%